Determinants of Non-oil Growth in the CFA-Zone Oil Producing Countries : How do they Differ? - Tabova, Alexandra (IMF Working Papers; Working Paper ;, 2011)
Non-oil growth in the CFA oil exporting countries has been lackluster despite their great natural resource wealth. In this paper we study the key determinants of non-oil growth and explore to what extent these countries differ from countries with comparable levels of development that do not depend on nonrenewable resources. Using a panel of 38 countries comprising LICs and CFA zone oil exporters, we find that while real exchange rate appreciation negatively impacted growth in all countries over the period 1985-2008, what distinguishes the oil producers of the CFA zone is the failure of public and private investment to spur non-oil growth.